Cross-border banking on the two sides of the Atlantic: Does it have an impact on bank crisis management? - Maria J. Nieto; Larry D. Wall (Federal Reserve Bank of Atlanta, 2015)
In the United States and the European Union (EU), political incentives to oppose cross-border banking have been strong in spite of the measurable benefits to the real economy from breaking down geographic barriers. Even a federal-level supervisor and safety net are not by themselves sufficient to incentivizing cross-border banking although differences in the institutional set-up are reflected in the way the two areas responded to the crisis. The U.S. response was a coordinated response, and the cost of resolving banks was borne at the national level. Moreover, the Federal Deposit Insurance Corporation (FDIC) could market failed banks to other banks irrespective of state boundaries, reducing the cost of the crisis to the U.S. economy and the sovereign finances. In the EU, the crisis resulted in financial market fragmentation and unbearable costs to some sovereigns. Moreover, the FDIC could market failed banks to other banks irrespective of state boundaries, reducing the cost of the crisis to the U.S. economy and the sovereign finances. In the EU, the crisis resulted in financial market fragmentation and unbearable costs to some sovereigns.
Keywords: G01; G21; G28; K20; L51; 330; cross-border banking; financial crisis; bankruptcy; European Union; United States